ASSESSMENT OF FLOW CHARACTERISTICS ALONG THE HYDRAULIC PHYSICAL MODEL OF A DAM SPILLWAY - Manogaran, Thiennieesh; Mohd Arif Zainol, Mohd Remy Rozainy; A. Wahab, Muhammad Khairi; Abdul Aziz, Mohd Sharizal; Zahari, Nazirul Mubin (Journal of Civil Engineering, Science and Technology, 2022)
Water flowing over a spillway has a very high kinetic energy because of the conversion of the entire potential energy to kinetic energy. This circumstance results in damage or significant erosion at the toes of the spillways, weir bed, and downstream of a river. To solve this problem, the water flow velocity must be minimised. Physical modelling was implemented to this conundrum in order to modify the current energy dissipating structure, the stilling basin, to enhance energy dissipation as much as achievable by downstream velocity reduction. Baffle blocks were adopted as the modification in this study because these are widely used to stabilize the jumps, shorten its length, and maximize energy dissipation. A selection of baffle arrangements was evaluated by positioning them in the stilling basin’s mid-span to identify the most effective outcome in minimizing downstream velocity. From the findings, it was clearly shown the arrangement of baffles blocks at the stilling basin impacts velocity reduction in various discharge cases. The formation of cross-waves was also assessed at the discharge channel at every discharge value with its relative distance from the sump and the width of the channel prior to the site. For discharge situations of 70.0 L/s and 100.0 L/s, modifications to the Type II stilling basin were recommended. Furthermore, constriction, expansion, or curvature should be avoided in chute spillways identical to the dam spillway to limit cross-wave generation and other unfavourable flow behaviours.